Oral Testosterone With and Without Concomitant Inhibition of 5α-Reductase by Dutasteride in Hypogonadal Men for 28 Days - Amory, John K. (J Urol, 2010)
PURPOSE: Co-administration of the 5α-reductase inhibitor dutasteride increases the oral testosterone bioavailability in men with experimentally induced hypogonadism. We examined oral testosterone with and without dutasteride administration in hypogonadal men for 28 days. MATERIALS AND METHODS: We randomly assigned 43 hypogonadal men to twice daily oral doses of 150, 250 or 400 mg testosterone with 0.25 mg dutasteride, 400 mg testosterone alone or 0.25 mg dutasteride alone for 28 days in a multicenter study. Subjects underwent pharmacokinetic profiling of serum hormones on days 1 and 28. A total of 32 men completed all study procedures. RESULTS: Serum testosterone increased in all groups on testosterone compared with that in the dutasteride only group. At the 400 mg dose the combination of testosterone and dutasteride resulted in average testosterone concentrations that were 2.7 and 4.6 times higher than in the testosterone only group on days 1 and 28, respectively (p <0.01). On day 28 average testosterone was 20% to 30% lower in all groups on testosterone and dutasteride, and 50% lower in the testosterone only group compared with day 1. Serum dihydrotestosterone was suppressed in all groups on dutasteride and increased in the testosterone only group. CONCLUSIONS: Oral testosterone administration resulted in a therapeutic serum testosterone concentration in hypogonadal men. Dutasteride improved the oral bio-availability of testosterone while suppressing dihydrotestosterone. Compared with day 1, testosterone was decreased after 28 days of administration. Additional study is warranted of oral testosterone with dutasteride for testosterone deficiency.